Effects of the COVID-19 pandemic on young people during the transition from school to training and work in Germany - Fernández Caruncho, Verónica [Verfasser] (My University, 2022)
„The effects of the COVID-19 pandemic have also left their mark on the transition from school to vocational training and work. Students with fairly low levels of school qualifications are particularly affected. Moreover, the cancellation of vocational orientation offers due to the pandemic, e.g. internships in companies, may have an impact on the matching of young people and their enrolment in training in the next school year. This article attempts to provide both an overview of the most important effects of the coronavirus pandemic at this transition stage and the approaches used by professionals and educational and counselling institutions through digital media and virtual activities to counteract these effects.“ (author’s abstract; BIBB-Doku)
Keywords: L 5 Beratung & Orientierung; G 1.3.2.2 Übergänge; P 2.3 Auszubildende; 370; Schüler; Berufsorientierung; Berufseinmündung; Erste Schwelle; Auszubildender; Ausbildungssituation; Pandemie